Blue Urea: Fertilizer With Reduced Environmental Impact - Driver, Justin G.; Owen, Rhodri E.; Makanyire, Terence; Lake, Janice A.; McGregor, James; Styring, Peter (Frontiers in Energy Research, 2019)
Synthetic nitrogen fertilizers such as urea are a necessity for food production, making them invaluable toward achieving global food security. Conventional manufacture of urea is conducted in centralized production plants at an enormous scale, with the subsequent prilled urea product distributed to the point-of-use. Despite consuming carbon dioxide in the synthesis, the overall process is carbon positive due to the use of fossil feedstocks, resulting in significant net emissions. Blue Urea could be produced using attenuated reaction conditions and hydrogen derived from renewable-powered electrolysis to produce a reduced-carbon alternative. This paper demonstrates the intensified production of urea and ammonium nitrate fertilisers from sustainable feedstocks, namely water, nitrogen and carbon dioxide. Critically, the process is scaled-down such that equipment can be housed in a standardized ISO container deployed at the point-of-use, delocalizing production and eliminating costs and emissions associated with transportation. The urea and ammonium nitrate were synthesized in a semi-continuous process under considerably milder conditions to produce aqueous fertilisers suitable for direct soil application, eliminating the financial and energetic costs associated with drying and prilling. The composition of the fertilisers from this process were found to be free from contaminants, making them ideal for application. In growth studies, the synthesized urea and ammonium nitrate were applied under controlled conditions and found to perform comparably to a commercial fertilizer (Nitram). Crucially, both the synthesized fertilisers enhanced biomass growth, nitrogen uptake and leaf chlorophylls (even in depleted soils), strongly suggesting they would be effective toward improving crop yields and agricultural output. The Blue Urea concept is proposed for installation in ISO containers and deployment on farms, offering a turnkey solution for point-of-need production of nitrogen fertilisers